2021
DOI: 10.3390/ijms22083855
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cold Atmospheric Pressure Plasma-Treated Media on the Cell Viability, Motility, and Induction of Apoptosis in Human Non-Metastatic (MCF7) and Metastatic (MDA-MB-231) Breast Cancer Cell Lines

Abstract: Breast cancer remains the most common type of cancer, occurring in middle-aged women, and often leads to patients’ death. In this work, we applied a cold atmospheric pressure plasma (CAPP)-based reaction-discharge system, one that is unique in its class, for the production of CAPP-activated media (DMEM and Opti-MEM); it is intended for further uses in breast cancer treatment. To reach this aim, different volumes of DMEM or Opti-MEM were treated by CAPP. Prepared media were exposed to the CAPP treatment at seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…According to the species of bacteria, the response to CAPP is different and actually, it's a species-dependent process and the Gram-positive bacteria is usually more susceptible to CAPs treatment because of the difference cell-wall components, which indicates that the CAPP-induced damage to the cell membrane and cell wall may be a key factor of antibacterial effect (9)(10)(11)(12)(13)(14)(15)(16)(17). Bacteria cause more than 60% of infection while they become more resistant to antimicrobial drugs every day, and often develop into a chronic state (8,18).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the species of bacteria, the response to CAPP is different and actually, it's a species-dependent process and the Gram-positive bacteria is usually more susceptible to CAPs treatment because of the difference cell-wall components, which indicates that the CAPP-induced damage to the cell membrane and cell wall may be a key factor of antibacterial effect (9)(10)(11)(12)(13)(14)(15)(16)(17). Bacteria cause more than 60% of infection while they become more resistant to antimicrobial drugs every day, and often develop into a chronic state (8,18).…”
Section: Introductionmentioning
confidence: 99%
“…Researches show that CAPP can increase their proliferation and distribution. And also, cold atmospheric pressure plasma can induce angiogenesis too (9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solutions treated with plasma are referred to as “plasma-activated medium (PAM)” [ 3 ], plasma-treated medium (PTM)” [ 4 ], “plasma-activated liquid (PAL)” [ 5 ], or “plasma-treated liquid (PTL)” [ 6 ]. These solutions contain reactive chemical species with a short half-life (e.g., reactive oxygen species (ROS) and reactive nitrogen species (RNS)) that can act as disinfectants [ 2 ] or anticancer agents [ 2 ].…”
mentioning
confidence: 99%
“…Terefinko et al [ 4 ] demonstrated PTM, produced by a cold atmospheric pressure plasma (CAP)-based reaction-discharge system, induces apoptosis in cancer cells, especially metastatic cells.…”
mentioning
confidence: 99%